Nephroprotective Activity of Ethanolic Extract of Papaya (Carica papaya) Seeds on Blood Urea Nitrogen and Creatinine Levels in Albino Rats Induced by Paracetamol - Muhammad Syahrul Mubarok; Gandul Atik Yuliani; Agus Sunarso; Nanik Hidayatik; Rochmah Kurnijasanti; Mirza Atikah Madarina Hisyam (Universitas Airlangga, 2025)
Kidney damage caused by high-dose paracetamol leads to elevated Blood Urea Nitrogen (BUN) and creatinine levels as indicators of impaired renal function. This study aimed to evaluate the dose-dependent nephroprotective effects of ethanolic Carica papaya seed extract on BUN and creatinine levels in paracetamol-induced albino rats. A posttest-only control group design was applied using 25 male Wistar rats divided into five groups: negative control (1% CMC-Na), positive control (paracetamol 1000 mg/kgBW), and three treatment groups receiving Carica papaya seed extract at doses of 100, 200, and 400 mg/kgBW. The extract was administered orally for seven consecutive days before paracetamol induction on day 8 and continued until day 11. Blood samples were collected on day 11, and serum was stored at -20 °C before BUN and creatinine concentrations were analyzed spectrophotometrically. Data were statistically analyzed using one-way ANOVA followed by Duncan’s Multiple Range Test (DMRT) at a significance level of p < 0.05. The results showed a significant and dose-dependent reduction in both parameters in all treated groups compared to the positive control, with the 400 mg/kgBW dose showing the strongest effect and restoring values close to physiological levels. The nephroprotective activity was associated with the antioxidant and anti-inflammatory mechanisms of the bioactive compounds that counteract oxidative stress and preserve renal cellular integrity. In conclusion, the ethanolic extract of Carica papaya seeds demonstrates significant dose-dependent nephroprotection against paracetamol-induced kidney injury in rats.